The Learned and Lived Law : Essays in Honor of Charles Donahue - Hatzimihail, Nikitas,; Kamali, Elizabeth Papp,; Lettmaier, Saskia, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This wide-ranging collection of essays reflects the manifold scholarly interests of legal historian Charles Donahue, whose former students engage here with questions related to foundational Roman law concepts, the impact of the law on women and families in medieval and early modern Europe, the intersection of law and religion, and the echoes of legal ideas on later developments in American law and in world literature and philosophy. From the monks of Metz to the book sellers of colonial Boston, from fourteenth-century English charters to the writings of Faust, these essays invite you to experience law at once learned and lived. Contributors are: Charles Bartlett, Anton Chaevitch, Wim Decock, Rowan Dorin, Sally E. Hadden, Elizabeth Haluska-Rausch, Nikitas Hatzimihail, Samantha Kahn Herrick, Daniel Jacobs, Elizabeth Papp Kamali, Amalia D. Kessler, Saskia Lettmaier, Sara McDougall, Stuart M. McManus, Elizabeth W. Mellyn, Bharath Palle, Ryan Rowberry, Carol Symes, James R. Townshend, and John Witte, Jr. See Less